The perceived transformation and transactional leadership styles among Tambon health promoting hospitals directors related to job satisfaction in Nakhonratchasima province, Thailand - Satayavongtip, Waranyou; Mongkolchati, Aroonsri; Srivanichakorn, Supattra (Journal of Public Health and Development, 2016)
Tambon Health Promoting Hospitals (THPHs) are the first level of public health service system. Before the health service system reform, the THPHs confronted with inefficient management. Leadership and job satisfaction in THPHs have been developed and expanded responsibilities to conform health system reformation in Thailand. This research aimed to identify the perceived transformation and transactional leadership behaviors among THPHs directors associated with their jobs satisfaction. A cross-sectional survey was conducted in 32 district health offices which consisted 349 directors of sub-districts health offices. The sample of 267 directors was randomly selected from Tambon Health Promoting Hospitals of Nakhonratchasima province, Thailand. The self-administered questionnaires were used to collect data by the mail survey which enclosed self-addressed stamped envelopes. The response rate was 100%. The survey period was limited in 30 days during April to May in 2013. The questionnaires composed of 3 parts: socio-economic factors, district public health officer leadership behaviors and job satisfaction which obtained reliability of 0.989 and 0.975. Descriptive statistics, Chi-square test and multiple logistic regression were used to analyze the data. This study found that overall satisfaction of directors in Tambon Health Promoting Hospitals were moderate level. They were proud of their work and found that their work were challenging (mean score of motivating factor=2.38), although their working conditions were not fully supporting them(mean score of hygiene factor = 2.13). After adjusting for confounding factors, this study found that the strongest factors were monthly salary factor (Adj. OR=2.379, 95% CI=1.169-3.850) and the perceived overall leadership style of transformation and transactional leadership within the high level (Adj. OR=70.801, 95% CI=8.691–576.804) significantly associated to job satisfaction among Tambon Health Promoting Hospitals directors (p-value<0.05). The management for training directors in Tambon Health Promoting Hospitals or in district healthcare centers should be focused mainly on job satisfaction. This has to be provided to meet their sufficient salary and overtime payments, sufficient personnel, and modern and standard instruments. To develop human capital of district health promoting hospital administrators, the directors of THPHS should emphasis on leadership development especially in promoting inspiration and conditional rewards.